(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The aim of the work is to investigate, on the basis of comparative case law, the future regulatory developments, not only in Italy, of cryopreservation as a complex legal phenomenon, with unknown traits, peculiar and innovative in the global panorama of comparative public law studies, the subject of analysis in other disciplines, mostly medical-scientific and technological.